2021
DOI: 10.3390/land10101043
|View full text |Cite
|
Sign up to set email alerts
|

The Ecosystem Services Value Change and Its Driving Forces Responding to Spatio-Temporal Process of Landscape Pattern in the Co-Urbanized Area

Abstract: The development of urbanization is still expanding on the earth, and the rapid expansion of cities has changed the regional landscape pattern and significantly affected the value of regional ecosystem services in developing countries such as China. Zhongmu County, as the core area of Zhengzhou-Kaifeng integration, studying the temporal and spatial transformations of its landscape pattern and ecosystem service value (ESV) is of great significance to the region’s sustainable development. Based on remote sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The enhance in PD reveals that the fragmentation of the landscape pattern in Wuhan improve during 2000-2015, leading to the decrease in the ESV. These results are consistent with many of previous studies (Yushanjiang et al, 2018;Zhang et al, 2021b). However, Chen et al (2021) and Liu et al (2020) found that an enhance in PD conduces to a reduce in ESV.…”
Section: Impacts Of Landscape Pattern On Esvsupporting
confidence: 92%
See 1 more Smart Citation
“…The enhance in PD reveals that the fragmentation of the landscape pattern in Wuhan improve during 2000-2015, leading to the decrease in the ESV. These results are consistent with many of previous studies (Yushanjiang et al, 2018;Zhang et al, 2021b). However, Chen et al (2021) and Liu et al (2020) found that an enhance in PD conduces to a reduce in ESV.…”
Section: Impacts Of Landscape Pattern On Esvsupporting
confidence: 92%
“…High landscape cohesion can cause an enhance in ecosystem services (Liu et al, 2020). However, other studies have shown that patch cohesion index has a negative effect on ESV (Zhang et al, 2021b;Guo et al, 2021).…”
Section: Impacts Of Landscape Pattern On Esvmentioning
confidence: 98%
“…This is similar to the research results in karst mountainous urban areas [ 58 ], but different from those in shallow hilly areas [ 53 ]. There is an obvious correlation between ESV and ecosystem types [ 59 , 60 ]: the high ESV was mainly distributed in natural ecosystems with better vegetation, while the low ESV was distributed in urban areas or harsh natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have primarily focused on the rise or fall of ESV caused by land use changes, but little is known about the driving mechanisms of ESV, particularly in arid areas [38,39]. Research methods for ESV and its driving factors have primarily included principal component and correlation analysis [40], regression models, and grey relational analysis [41]. Although these methods can explain the contribution of influencing factors to a certain extent, they fail to capture the interaction and joint effects between influencing factors and cannot fully express the complex spatial correlation and spatiotemporal differentiation characteristics within ESV [42].…”
Section: Introductionmentioning
confidence: 99%